1862-1863 N.C. Sess. Laws 60 - (:unkn) unknown (My University, 1862)
Priv. Laws, Adj. Sess., ch. 49, § 9: [T]hey may prohibit and prevent by practices the riding or driving of horses or other animals at a speed greater than six miles an hour, within the city; and also the firing of guns, pistols, crackers, gun powder or other explosive, combustible or dangerous materials in the streets, public grounds, or elsewhere within the city.
Keywords: DISCHARGE